Remote Monitoring Systems for Patients with Chronic Diseases in Primary Health Care - Peyroteo, Mariana (2022)
Funding Information: MP received support from the Portuguese National Funds through FITEC – Programa Interface, with reference CIT INOV – INESC INOVAÇÃO. Funding was also provided from the PhD program in Industrial Management, NOVA Science and Technology Faculty. Funding Information: MP and LVL acknowledge Fundação para a Ciência e a Tecnologia (FCT-MCTES) for its financial support via the project UIDB/00667/2020 (UNIDEMI).